Defining a Leader Role curriculum for radiation oncology: A global Delphi consensus study. Issue 2 (May 2017) - Turner, Sandra; Seel, Matthew; Trotter, Theresa; Giuliani, Meredith; Benstead, Kim; Eriksen, Jesper G.; Poortmans, Philip; Verfaillie, Christine; Westerveld, Henrike; Cross, Shamira; Chan, Ming-Ka; Shaw, Timothy
Abstract: Background and purpose: The need for radiation oncologists and other radiation oncology (RO) professionals to lead quality improvement activities and contribute to shaping the future of our specialty is self-evident. Leadership knowledge, skills and behaviours, like other competencies, can be learned (Blumenthal et al., 2012). The objective of this study was to define a globally applicable competency set specific to radiation oncology for the CanMEDS Leader Role (Frank et al., 2015). Methods: A modified Delphi consensus process delivering two rounds of on-line surveys was used. Participants included trainees, radiation/clinical oncologists and other RO team members (radiation therapists, physicists, and nurses), professional educators and patients. Results: 72 of 95 (76%) invitees from nine countries completed the Round 1 (R1) survey. Of the 72 respondents to RI, 70 completed Round 2 (R2) (97%). In R1, 35 items were deemed for 'inclusion' and 21 for 'exclusion', leaving 41 'undetermined'. After review of items, informed by participant comments, 14 competencies from the 'inclusion' group went into the final curriculum; 12 from the 'undetermined' group went to R2. In R2, 6 items reached consensus for inclusion. Conclusion: This process resulted in 20 RO Leader Role competencies with apparent global applicability. This is the first step towards developing learning, teaching and assessment tools for this important area of training.